INFLUENCES OF DECREPIT GYNMNASTIC EXERCISE TOWARD BLOOD TENSION OF HYPERTENSION PATIENTS AGE 40 AND OVER - Noortje Anita Kumaat, (Kepelatihan Olahraga, 2009)
At women aged 40 blood tension may not be more than 140/90, if so they will be categorized as hypertension patient. Risks occurred at the patient include increasing stroke risk, heart attack, and other health troubles such as peripheral circulation, train vascular problem and also retina. Appropriate sport for hypertension patients is decrepit gymnastic, beside its motion is itnitable; it is also good for senior citizens and can decrease blood tension of hypertensive individuals. As defined above the research concluded that there are influences of decrepit gymnastics toward blood tension of women hypertension patients aged 40 and over. The research was aimed to understand influences of decrepit gymnastic toward blood tension of hypertension patients aged 44 and over. And the issue was formulated as follows: is there influence decrepit gymnastic toward blood tension of hipertensive individuals aged 40 and over. This research method used population research. The independent varlabel is decrepit gymnastic and that of dependent is hypertension. Population in the research are women aged 40 of hypertension patients in Decrepit Gymnastic in Kedurus Surabaya. And the taken samples are 10 individuals. Blood tension was taken using tensiometer/sphygmomanometer. The research concluded that result of sistole t-calculation 13.42 was greater than t-table 2.262 on signification stage 0.05, dk; 9 and t-calculation diastole 9.64 was greater than t-table 2.62 on signification stage 0.05 and dk; 9, from these result it can be concluded that There are influences decrepit gymnastic toward blood tension of hypertension patients before and after.